2014
DOI: 10.1242/jcs.147926
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular cleavage of E-cadherin promotes epithelial cell extrusion

Abstract: BSTRACTEpithelial cell extrusion and subsequent apoptosis is a key mechanism to prevent the accumulation of excess cells. By contrast, when driven by oncogene expression, apical cell extrusion is followed by proliferation and represents an initial step of tumorigenesis. E-cadherin (E-cad), the main component of adherens junctions, has been shown to be essential for epithelial cell extrusion, but its mechanistic contribution remains unclear. Here, we provide clear evidence that cell extrusion can be driven by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 67 publications
3
71
2
Order By: Relevance
“…However, the initial step of this process is not clearly understood and remains a 'black box' in cancer biology; when the first mutation occurs in a single cell within epithelia, what happens next? Recent studies have revealed that Ras-, Src-or ErbB2-transformed cells are apically extruded from a monolayer of normal epithelial cells (Grieve and Rabouille, 2014;Hogan et al, 2009;Kajita et al, 2010;Leung and Brugge, 2012;Wu et al, 2014) and that perturbation of proper epithelial organization suppresses this anti-oncogenic process (Hogan et al, 2009;Kajita et al, 2014). During the process of apical extrusion, various signaling pathways are activated in both normal and transformed cells in a non-cell-autonomous fashion.…”
Section: Introductionmentioning
confidence: 99%
“…However, the initial step of this process is not clearly understood and remains a 'black box' in cancer biology; when the first mutation occurs in a single cell within epithelia, what happens next? Recent studies have revealed that Ras-, Src-or ErbB2-transformed cells are apically extruded from a monolayer of normal epithelial cells (Grieve and Rabouille, 2014;Hogan et al, 2009;Kajita et al, 2010;Leung and Brugge, 2012;Wu et al, 2014) and that perturbation of proper epithelial organization suppresses this anti-oncogenic process (Hogan et al, 2009;Kajita et al, 2014). During the process of apical extrusion, various signaling pathways are activated in both normal and transformed cells in a non-cell-autonomous fashion.…”
Section: Introductionmentioning
confidence: 99%
“…In human cancers, MMP-14 co-localizes with laminin-5, which suggests that it is associated with microinvasive cancers [68]. E-cadherin is cleaved by MMP-3 or 7, and the release of E-cadherin promotes the invasion of tumor cells in a paracrine manner in vitro, possibly acting as a competitive inhibitor of other E-cadherin [69]. Cleavage of Ecadherin also triggers epithelial to mesenchymal transition associated with the invasive behavior of tumors, including metastatic melanomas [69].…”
Section: Matrix Metalloproteinasesmentioning
confidence: 99%
“…E-cadherin is cleaved by MMP-3 or 7, and the release of E-cadherin promotes the invasion of tumor cells in a paracrine manner in vitro, possibly acting as a competitive inhibitor of other E-cadherin [69]. Cleavage of Ecadherin also triggers epithelial to mesenchymal transition associated with the invasive behavior of tumors, including metastatic melanomas [69]. Other molecules such as CD44, also regulate this process [70].…”
Section: Matrix Metalloproteinasesmentioning
confidence: 99%
“…E-cadherin and actomyosin contractility are important players in extrusion. A recent study showed that cleavage of the extracellular domain of E-cadherin is a mechanism driving cell extrusion (Grieve and Rabouille, 2014). N-WASP has also been implicated in extrusion.…”
Section: Oncogenic Cell Extrusionmentioning
confidence: 99%
“…N-WASP has also been implicated in extrusion. Extruding cells have been shown to harbour increased cortical Factin intensity compared to neighbouring cells (Grieve andRabouille, 2014, Wu et al, 2014). In H-Ras V12 transformed cells cultured among wild type cells, N-WASP was found to redistribute to areas of contact (lateral adherens) and was depleted from the zonula adherens (Wu et al, 2014).…”
Section: Oncogenic Cell Extrusionmentioning
confidence: 99%